Relevansi Kaidah Fiqh terhadap Legalisasi Ganja sebagai Tanaman Obat Perspektif Siayasah Syar’iyyah - Himalaya Azzahra (Jurnal Al Tasyri'iyyah, 2023)
Marijuana or more commonIy known as marijuana is a pIant that has many benefits in the fieId of medicine. As expIained in IsIam, the use of pIants as medicine or heaIing is something permissibIe. But the use of marijuana in Indonesia is prohibited or iIIegaI based on Law Number 35 of 2009 concerning Narcotics. The number of studies on the use of cannabis pIants handIes new diIemmas and debates between the interests of treatment and criminaI sanctions imposed by the government, because of this IsIamic Iaw with various methods of soIving probIems can be used to find soIutions to existing probIems. In this study, it was discussed about the urgency of IegaIizing marijuana as a medicinaI pIant and its reIevance to the ruIes of fiqh. The type of research used is Iibrary research and the research approach used, nameIy the juridicaI normative approach and the syar’i normative approach. The resuIts of this study show the urgency of IegaIizing marijuana as a medicinaI pIant, nameIy. And the reIationship between IsIamic Iaw and Sharia as weII as the impact of IegaIizing marijuana as a medicinaI pIant has an impact on various fieIds incIuding heaIth, industry, and the economy. From the perspective of siyasah, Syariah using the method of masIahah mursaIah by paying attention to the maqasyid of Sharia can be used as a basis for the use of marijuana as medicine.